The city/country relationship in spanish children's literature dystopias: what alternatives for the future os Spain? - Mauclair, Patricia (Ondina - Ondine, 2022)
Using anticipation to redefine ecological challenges is not surprising in literature aimed at the young people we seek to prepare for the future. It would therefore be logical for the dystopias written in the twenty-first century in a Spain preoccupied with the sprawling expansion of the city and the desertification of the countryside to encourage a reinvention of the relationship between city and country. We will attempt to see here whether they have succeeded in doing so.Key words: young adult novel, dystopia, ecology, city